1986
DOI: 10.1111/j.1476-5381.1986.tb10218.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent inhibition of platelet aggregation

Abstract: In cascade perfusion and superfusion experiments on rabbit tissues, when acetylcholine (ACh) was introduced into the circuit so as to perfuse the aorta under perfusion with noradrenaline (NA), the effluent relaxed the transverse aortic strip which had been denuded of endothelium. The effluent from the perfused aorta which was capable of relaxing the transverse aortic strip also significantly inhibited platelet aggregation induced by arachidonic acid (AA) in a volume‐related manner. The inhibitory activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
200
0
6

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(210 citation statements)
references
References 14 publications
4
200
0
6
Order By: Relevance
“…In addition, when the production of prostacyclin is abolished by indomethacin, stimulation of the endothelium induces the release of EDRF which inhibits platelet aggregation (Azuma et al, 1986;Furlong et al, 1987;Radomski et al, 1987). We have recently shown that the release of NO accounts for the vascular relaxation attributed to EDRF .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when the production of prostacyclin is abolished by indomethacin, stimulation of the endothelium induces the release of EDRF which inhibits platelet aggregation (Azuma et al, 1986;Furlong et al, 1987;Radomski et al, 1987). We have recently shown that the release of NO accounts for the vascular relaxation attributed to EDRF .…”
Section: Discussionmentioning
confidence: 99%
“…EDRF also inhibits platelet aggregation (Azuma et al, 1986;Furlong et al, 1987;Radomski et al, 1987). We have recently demonstrated that nitric oxide (NO) is released by vascular endothelial cells in amounts sufficient to account for the vasodilator properties of EDRF .…”
Section: Introductionmentioning
confidence: 99%
“…Endothelium-derived relaxing factor (EDRF) mediates the vasodilator effect of acetylcholine (ACh) and a number of other substances on isolated blood vessels (Furchgott, 1984) and exhibits potent platelet anti-aggregatory activity both in vitro (Azuma et al, 1986) and in vivo Hogan et al, 1988). Evidence has been presented in the literature that EDRF is identical with nitric oxide (NO) (Palmer et al, 1987) and is formed from L-arginine (Palmer et al, 1988a).…”
Section: Introductionmentioning
confidence: 96%
“…The vascular relaxation induced by EDRF is mediated by the stimulation ofsoluble guanylate cyclase and the consequent rise in guanosine 3': 5'-cyclic monophosphate (cyclic GMP) levels (Rapoport et al, 1983). EDRF has also been reported to inhibit platelet aggregation (Azuma et al, 1986;Furlong et al, 1987).…”
Section: Introductionmentioning
confidence: 99%